Analysis of the Need for Mechanical and Instrumentation Equipment in the Utilization of Gas Wells in Balun Field - Kasturi; Suharyadi, Hafid; Mulyono, Dwi (Politeknik Energi dan Mineral Akamigas, 2021)
The utilization of old gas wells in Balun field has the potential to improve the welfare of the people in Cepu District and the surrounding areas in meeting their daily gas needs. However, the challenge of these old unutilized gas wells has risks and impacts on the environment, such as the possibility of gas leak causing fires. This study aimed to analyze the potential of old gas wells and to analyze the impact of risks on the areas around the old gas wells, which will be passed through the gas network, and where the gas processing units will be established. In this analysis, the results of the gas processing process would be distributed to Cepu District to meet household fuel needs. In addition, the use of these old gas wells is also to provide education to students regarding gas processing and distribution. The analysis of the utilization of old gas wells began with mapping of environmental conditions, distribution pipeline systems, and gas processing locations. The mechanical equipment requirements for the model, pipeline design, and processing unit would be presented. Next, the need for the instrumentation system would improve the transmission system and processing unit with reference to ease of operation and safety. In addition, budget requirements and flow diagram were needed to facilitate further programs when building pipelines and the desired gas processing unit